Cross kill : an Alex Cross story - Patterson, James, 1947- (New York : Bookshots/Little, Brown and Company, 2016)
Along Came a Spider killer Gary Soneji has been dead for over ten years. Alex Cross watched him die. But today, Cross saw him gun down his partner. Is Soneji alive? A ghost? Or something even more sinister? Nothing will prepare you for the wicked truth.
Includes a sneak peek for The trial.
Keywords: Cross, Alex (Fictitious character) -- Fiction; Police -- Washington (D.C.) -- Fiction; African American detectives -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction